THE PERSPECTIVES OF SAME-SEX PARENTING IN SERBIA: BETWEEN NEEDS AND OPPORTUNITIES - Vlašković, Veljko; Arsić, Jelena - (Pravni zapisi, 2022)
In the context of current aspirations in terms of drafting and adoptinga regulation that would finally legalize same-sex unions in Serbia, particularlyimportant issue relates to the effect of same-sex union on the legalposition of a child in such unity. The recently published text of the DraftLaw on Same-Sex Unions undoubtedly opens the space for consideringcertain solutions related to the rights and obligations of a same-sex partnerof a parent of the child, which is of direct importance in terms of exercisingrights of the child in family relations. Based on these provisions,the authors seek to analyze legal possibilities and restrictions regardingthe regulation of parental duties and rights of the child in the context ofsame-sex unions in Serbia. In these efforts, the authors commence fromthe relevant legal framework that regulates family relations, and therebyindicate some possible solutions.
Keywords: same-sex union; same-sex partner; parenting; child; best interests of the child